Potensi Lamun di Kampung Aisandami Kabupaten Teluk Wondama dan Strategi Pengelolaanya - Selvi Tebay; Paulus Boli; Joiner F Ainusi (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2020)
Seagrass ecosystem have primary and secondary productivity with great support to the abundance and diversity of fishes and it’s biota associations. Seagrass ecosystems are also as a coastal resources that have an important role of environmental services. Some community activities will directly or indirectly can have an impact on habitat degradation and biodiversity of seagrass ecosystems. The importance oto assess the potential of seagrass ecosystem and it’s biotas association is to know of sea grass’s role to provides of environmental services is the aim of this study. This research was conducted in the waters of Kampung Aisandami, Teluk Wondama Regency during June - July 2019. Data collection methodology was used is structured random methods quadrant transects at two observations to reveal data on seagrass community structure. The datas obtained were tabulated and displayed in tables and figures. Thalassia hemprichii and Enhalus acoroides were found at two observation sites. Another type found outside the observation transect is Halophila ovalis. E. acoroides seagrass species have a frequency value is 0.77 which shows that distribution of E. acoroides is wider than T. hemprichii which has a frequency is 0. 58. Both of station show that T. hemprichii has a frequency value of 0.7 where it indicates that distribution is wider compare with E. Acoroides. T hemprichii has the highest relative density at both observation stations. The status of seagrass of both stations is classified as poor or unhealthy with seagrass value ≥ 30-59.9%. The highest importance index is the T. hemprichii seagrass at both stations and has a higher role than the E. acoroides. The community-based management model is the a suitable model that can be used to developing coastal ecosystem management including seagrass ecosystems in this village.